2017
DOI: 10.25252/se/17/41133
|View full text |Cite
|
Sign up to set email alerts
|

Effect of textile wastewater on growth and yield of wheat (Triticum aestivum L.)

Abstract: Textile wastewater can be a good source of nutrients in addition to meet the crop water requirements in areas facing water shortage problem. The use of untreated industrial wastewater can be hazardous for end users and soil environment due to high concentration of pollutants. The toxic effects of wastewater could be reduced by dilution of these pollutants. A pot trial was conducted to evaluate the suitability of untreated textile wastewater at different dilution levels (0, 10, 20, 30, 40, 50, 60, 70, 80, 90 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…As well as the SW was diluted with good quality groundwater (67) figure (11), there was a slight improvement in SW quality, but it still remained at the medium level (50). Even though the best dilution ratio of 1:1 was utilized in this study, as determined by the results of [16,17] also found that the pollutants in the wastewater were reduced with a 1:1 dilution. To be more suitable in using for drip irrigation the diluted sedimented wastewater (DSW) passed through the biochar filter, the FISWQI-I increased to 61.59 (Good quality), as shown in figure (11).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…As well as the SW was diluted with good quality groundwater (67) figure (11), there was a slight improvement in SW quality, but it still remained at the medium level (50). Even though the best dilution ratio of 1:1 was utilized in this study, as determined by the results of [16,17] also found that the pollutants in the wastewater were reduced with a 1:1 dilution. To be more suitable in using for drip irrigation the diluted sedimented wastewater (DSW) passed through the biochar filter, the FISWQI-I increased to 61.59 (Good quality), as shown in figure (11).…”
Section: Resultsmentioning
confidence: 71%
“…Dilution of wastewater with fresh water is another smart alternative that conserves fresh water used for irrigation and addresses the problem of water scarcity in arid and semi-arid areas. Diluted wastewater has a lesser impact on plants, especially when mixed at a ratio of 1:1, which is considered the best dilution factor for wastewater reuse [16,17]. Another method for treating wastewater is the application of biochar filters.…”
Section: Introductionmentioning
confidence: 99%
“…The fatal effects of heavy metals in plants are related to the restricted elementary biological practices such as photosynthesis, mineral nutrition, water relation, as well as by mass production of radicals, lipid peroxides, superoxides, etc. [3].…”
Section: Introductionmentioning
confidence: 99%